2019
DOI: 10.2147/pgpm.s211490
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of MTHFR and ABCC2 gene polymorphisms on antiepileptic drug responsiveness in Jordanian epileptic patients</p>

Abstract: Background Epilepsy is one of the most common neurological diseases with unclear etiology where its genetic background and treatment regime still need further exploration. Objectives This study designed to evaluate the pharmacogenomics of MTHFR and ABCC2 genes, and their association with epilepsy susceptibility among Jordanian population. Methods A case-control study was conducted on Jorda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 52 publications
1
22
1
Order By: Relevance
“…Treatment of seizures in AD with low-dose antiepileptic drugs (AEDs) is usually well tolerated and efficacious, and selected AEDs might also help in slowing-down disease progression [269,270]. Anticonvulsants may suppress seizures in up to two-thirds of all patients, with no apparent effects on long-term prognosis [271].…”
Section: Epilepsymentioning
confidence: 99%
“…Treatment of seizures in AD with low-dose antiepileptic drugs (AEDs) is usually well tolerated and efficacious, and selected AEDs might also help in slowing-down disease progression [269,270]. Anticonvulsants may suppress seizures in up to two-thirds of all patients, with no apparent effects on long-term prognosis [271].…”
Section: Epilepsymentioning
confidence: 99%
“…However, this study encountered some limitations such as small sample size and focusing on genotyping certain polymorphisms. Moreover, only a few pharmacogenetic studies [33][34][35][36][37][38][39][40][41][42][43][44] have been conducted in Jordan. Therefore, more studies are recommended in this topic by investigating other VIP variants in different candidate genes.…”
Section: Discussionmentioning
confidence: 99%
“…5 To date, there is a limited number of studies investigating the genetic and pharmacogenetic basis of common diseases, including epilepsy among the Jordanian population. [6][7][8][9][10][11] Recent studies found that epilepsy is associated with several chromosomal regions, where mutations in these regions cause neurological dysfunction. 12 The solute carrier gene, SLC1A1, is a high-affinity glutamate transporter that is associated with neurodevelopmental phenotypes, such as myoclonic-atonic epilepsy and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%